Hormone-sensitive lipase: sixty years later - Recazens, Emeline; Mouisel, Etienne; Langin, Dominique (Progress in lipid research, 2021)
Hormone-sensitive lipase (HSL) was initially characterized as the hormonally regulated neutral lipase activity responsible for the breakdown of triacylglycerols into fatty acids in adipose tissue. This review aims at providing up-to-date information on structural properties, regulation of expression, activity and function as well as therapeutic potential. The lipase is expressed as different isoforms produced from tissue-specific alternative promoters. All isoforms are composed of an N-terminal domain and a C-terminal catalytic domain within which a regulatory domain containing the phosphorylation sites is embedded. Some isoforms possess additional N-terminal regions. The catalytic domain shares similarities with bacteria, fungus and vascular plant proteins but not with other mammalian lipases. HSL singularity is provided by regulatory and N-terminal domains sharing no homology with other proteins. HSL has a broad substrate specificity compared to other neutral lipases. It hydrolyzes acylglycerols, cholesteryl and retinyl esters among other substrates. A novel role of HSL, independent of its enzymatic function, has recently been described in adipocytes. Clinical studies revealed dysregulations of HSL expression and activity in disorders, such as lipodystrophy, obesity, type 2 diabetes and cancer-associated cachexia. Development of specific inhibitors positions HSL as a pharmacological target for the treatment of metabolic complications.
Keywords: Diabetes Mellitus, Type 2; tuková tkáň; Hormone-sensitive lipase; Adipocytes; Animals; Sterol Esterase; tukové buňky; sterolesterasa; Lipolysis; lipids; lipodystrophy; lipolysis; diabetes mellitus 2. typu; obesity; zvířata; Adipose Tissue; lipolýza